Doppler Waveform Abnormalities of Hepatic Veins with Histological Changes in Chronic Hepatitis - C Infection - Areej Amber Khan , Hina Nasir, M Habib Afzaal, Samia Amin (Journal of Rawalpindi Medical College, 2016)
Background :.To study the diagnostic accuracy of the abnormalities in Doppler waveform of hepatic veins by comparing with histological changes in chronic liver disease (HCV infection). Methods: In this cross sectional study 150 patients with chronic hepatitis C infection were included. Patients were subjected to real time Ultrasound and Doppler scanner, Using a 3.75 MHZ sector transducer through a trans-abdominal approach . The sample volume, as large as at least one third of the vessel’s diameter, was positioned within the middle hepatic vein at a distance of 3-6 cm from the outlet into the inferior vena cava. Histopathology results were taken as gold standard. The New Inuyama scoring system was used to assess the fibrosis stage. The sensitivity, specificity, positive predictive value (PPV) and negative predictive values (NPV) were calculated for Doppler US. Data was analyzed by SPSS version 14. Results: In our study the diagnostic accuracy of the abnormalities in Doppler waveform of hepatic veins by comparing with histological changes (gold standard) in chronic liver disease (HCV infection) was calculated in 79%, sensitivity 86%, specificity 61%, PPV 83% and NPV 67% Conclusion:The study concludes that Doppler ultrasound is equally a very reliable and dependable technique for the validation of Doppler ultrasonography of hepatic veins in diagnosis of chronic liver disease due to HCV infection as histopathological grading.